Korelasi Aktivitas Siswa dalam Proyek dan Hasil Belajar Psikomotorik pada Instalasi Penerangan Listrik - Risan Alfaruky; Sukardi (Departement of Electrical Engineering Universitas Negeri Padang, 2025)
This study aims to analyze the correlation between student activities in Project-Based Learning (PjBL) and psychomotor learning outcomes in the Electrical Lighting Installation subject at SMKN 1 Pariaman. The research is motivated by the gap between students' theoretical understanding and practical skills, particularly in wire connection, circuit testing, and the use of measuring instruments. The low psychomotor skills of vocational students contribute to the high unemployment rate among graduates, as indicated by BPS data showing an open unemployment rate of nine point zero one percent. This study employs a quantitative approach with a correlational method, involving twenty-one students from class XI of the Electrical Power Installation Engineering program. Data were collected through questionnaires to measure student project engagement and observation sheets to assess psychomotor performance during practical installation tasks. The data were analyzed using normality, linearity, and Pearson Product Moment correlation tests. The results revealed a significant positive correlation between student involvement in project activities (including planning, component installation, and evaluation) and improved psychomotor skills, particularly in precision, compliance with technical standards, and occupational safety practices. These findings underscore the importance of implementing PjBL in vocational education to enhance students' practical competencies. Therefore, it is recommended that teachers facilitate more structured and industry-relevant project-based learning to better prepare vocational students for careers in the electrical field.